The Effect of Corporate Social Responsibility, Voluntary Disclosure, Leverage, and Timeliness on Earnings Response Coefficient - Dirvi Surya Abbas; Arry Eksandy; Imam Hidayat (Profesional Muda Cendekia Publishing, 2020)
The purpose of this study was to determine the effect of corporate social responsibility, voluntary disclosure, leverage, and timeliness on earnings response coefficient at LQ45 companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 3 years, namely the 2015-2017 period. The population of this study includes all LQ45 companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2017 period. The sampling technique was using purposive sampling technique. Based on the predetermined criteria, 10 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that corporate social responsibility, voluntary disclosure, leverage and timeliness had no effect on earnings response coefficient.